2016
DOI: 10.1097/scs.0000000000002300
|View full text |Cite
|
Sign up to set email alerts
|

Dermoid Cyst of the Lateral Neck Included Within the Submandibular Gland

Abstract: Dermoid cysts are benign lesions of congenital origin, and those in the head and neck region are usually present as a midline neck mass. They rarely appear in the lateral neck. This article describes the clinical presentation and histopathologic features of an extremely rare case of lateral dermoid cyst included within the submandibular gland in a 58-year-old man. The etiology of the cyst is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Overall, the prognosis for these lesions was good when complete surgical resection was achieved. Many authors reported no recurrence in their series, and the patients recovered very well [10,15,31].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Overall, the prognosis for these lesions was good when complete surgical resection was achieved. Many authors reported no recurrence in their series, and the patients recovered very well [10,15,31].…”
Section: Discussionmentioning
confidence: 88%
“…It is the second most common midline neck cyst, representing 25% of all congenital cystic masses of the neck [18,40]. Despite its congenital origin, an acquired etiology was also reported to account for 10% of dermoid cysts due to trauma or implantation of epithelial cells in utero [15]. Dermoid cysts may occur anywhere in the body, with approximately 7% of cases reported in the head and neck [5].…”
Section: Discussionmentioning
confidence: 99%
“…Dermoid cysts are benign congenital lesions occurring in about 80% in the ovaries and testicles and only 1.6-7% are found in the head and neck region, mainly in the midline of the body [5,6]. Most of these lesions found in the cervicofacial region are congenital and they are derived from entrapment of epithelial cells during midline fusion in embryonic development [7,8].…”
Section: Introductionmentioning
confidence: 99%